Dielectric qualities temperature dependencies of lithium-titanium ferrite ceramic; Proceedings of 12th International Conference on radiation physics and chemistry of Inorganic materials, 23-27 September 2003, Tomsk - Malyshev A. V. (2003, 2003)
В фонде НТБ ТПУ отсутствует